Pengaruh Model Pembelajaran Project Based Learning (PjBL) Terhadap Kemampuan Berpikir Kreatif Siswa - Nur Aisyah Pulungan; Khairuna Khairuna (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to improve students' creative thinking skills through the PjBL (Project Based Learning) learning model on the digestive system material at Smart Pure High School. The research method is quantitative using a quasi-experimental design with a nonequivalent control group design. The population in this study were students of class XI SMA Smart Murni which consisted of 2 classes with a total of 61 students, where the control class, namely XI MIPA 1, consisted of 30 students and class XI MIPA 2 as the experimental class which consisted of 31 students. As for the data analysis technique used to test the hypothesis in the study using the t-test independent data this study used an instrument in the form of an essay test for creative thinking skills. The results showed that the average value obtained for the control class was 70.10 and for the experimental class it was 81.04. Then a t test was carried out to prove that the difference was significant (real) or not, where the Sig.(2-tailed) value was 0.000 <0.05. In conclusion, in descriptive statistics there is a difference in the average creative thinking ability of students between the experimental class and the control class. Based on the results of the T test, there is a significant difference in PjBL (Project Based Learning) learning towards improving students' creative thinking skills. Keywords: Creative Thinking, Project Based Learning, Digestive System